UPM-APSB's AISA hyperspectral imaging for individual mangrove species mapping in Port Klang / Kamaruzaman Jusoff - Jusoff, Kamaruzaman (2006)
Every natural and synthetic object on the earth's surface and near surface reflects and emits electromagnetic radiation (EMR) over a range of wavelengths in its own characteristic way according to its chemical composition and physical state. With a narrow contiguous 288 maximum bands ranging from visible (VIS) to near infra-red (NIR) wavelength region available on hyperspectral sensors, a particular object/feature or condition often exhibits a diagnostic spectral response pattern that differs from other objects. The objectives of this study are therefore to assess the capability of AISA airborne hyperspectral imaging for individual mangrove species mapping and to determine the wavelength regions that define the inherent spectral characteristics amongst mangrove species. A total of nine groups of mangrove species spectral separability from 19 selected mangrove trees were identified in Port Klang, Selangor namely, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, Avicennia officials, Rhizophora apiculata, Bruguiera parviflora, Bruguiera gymnorhiza, Bruguiera cylindrical and Sonneratia caseolaris. The nine groups of individual mangrove species were easily identified and separated in the NIR range (700 nm to 900 nm) with the following spectral values namely (a) 1,750-6,000: Bruguiera cylindrical, (b) 2,000-7,750: Bruguiera gymnorhiza, (c) 1,875-8,250: Bruguiera parviflora, (d) 1,875-5,500 :Avicennia officials, (e) 1,625-6,250 :Sonneratia caseolaris, (f) 1,875-5,250: Sonneratia alba, (g) 1,750-7,500. Rhizophora apiculata, (h) 2,000-8,000: Rhizophora stylosa, (i) 2,200-7,000: Rhizophora mucronata. The results of this study indicated that the mangrove species under study could only be identified at the near infrared (NIR) wavelength (700 nm to 900 nm) and not in the visible (VIS) spectrum.